Lithium-based silicone oil homogeneous sealing material, preparation method and application thereof
Patent Information
- Application Number
- CN202611153364.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明的目的在于提供一种锂基硅油均相密封材料及制备方法和应用,以解决上述背景技术中提出的现阶段锂基硅油密封材料难以满足高端机械装备长寿命、高稳定、宽温域、高负载的严苛使用需求,极大限制了锂基润滑脂在高端工业领域的深化应用,普遍存在微观结构不均、耐极端工况能力弱、长效使用可靠性差等问题
1.本发明以环硅氧烷作为化学结构调控剂,在高温(180~200℃)条件下诱导体系内发生硅氧烷重排反应——环硅氧烷开环后与硅油分子链、锂皂表面活性位点发生化学键合或强物理缠结,从分子层面消除了硅油相与锂皂相之间的界面张力,使体系由非均相结构转变为热力学稳定的均相结构,并在此基础上实现了锂基稠化剂、PTFE与气相白炭黑的多尺度协同增强,获得了综合性能显著优于现有技术的密封材料,彻底消除储存、高温静置过程中的渗油、分层失效风险,解决现有技术无法根除的胶体安定性短板。
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sealing materials, specifically relating to a lithium-based silicone oil homogeneous sealing material and its preparation method, as well as its application in automotive component sealing and structural sealing under high-temperature conditions of 150-300℃. Background Technology
[0002] Lubricating grease, as a core component of mechanical friction pairs and sealing structures, is widely used in automobiles, home appliances, plastic components, high-temperature sealing, and other fields. Based on its thickening system, it can be divided into three main categories: silicone-based inorganic thickened grease, lithium soap-based grease, and silicone oil-lithium soap composite grease. Among them, lithium-based grease is a lubricating material made by thickening base oil with lithium hydroxy fatty acid soap and adding various additives. Due to its excellent chemical stability, high and low temperature resistance, and water resistance, it is widely used in the sealing and lubrication of various mechanical systems. However, existing lithium-based silicone oil sealing materials still have the following significant technical shortcomings in practical applications: 1. Poor compatibility and structural stability: In traditional lithium-based silicone oil sealing materials, the silicone oil base oil has weak polarity, while the lithium soap (thickener) has strong polarity. Due to the significant difference in polarity, the compatibility between silicone oil and the lithium saponified structure is limited. This inherent polarity mismatch easily leads to phase separation during storage or use, i.e., "oil separation," thereby compromising the structural stability of the sealing material.
[0003] 2. Failure Risks Under Harsh Operating Conditions: Under harsh operating conditions such as heavy loads, high-speed rotation, and drastic temperature changes (e.g., -40℃ to above 200℃), traditional materials struggle to maintain a stable structural state over the long term. Due to insufficient structural stability, materials are prone to softening and loss or hardening failure, leading to decreased sealing performance and failing to meet the requirements for long service life and high reliability.
[0004] 3. Difficulty in constructing a homogeneous structure: In existing technologies (such as some common silicone-based greases), thickeners are often dispersed in the base oil through simple physical mixing, lacking effective structural control methods. Although some existing technologies introduce fumed silica as a stabilizer, without the participation of chemically controlled components, it is difficult to form a uniform, continuous, and stable three-dimensional network structure at the microscopic level, resulting in limited mechanical stability and shear resistance of the material. For example, patent document CN106635347A discloses a high-performance silicone-based grease composition and its preparation method, which uses methyl / phenyl silicone oil as the base oil, fumed silica as the thickener, and adds esters or alcohols as stabilizers. Although this solves some PVC compatibility issues, its thickening system mainly relies on fumed silica and does not involve the homogeneous construction of lithium soap and silicone oil. Furthermore, alcohol / ester stabilizers are prone to volatilization or decomposition at high temperatures, making it difficult to meet the ultra-high temperature conditions of 300℃. For example, patent document CN114703004A discloses a lithium-based grease composition and its preparation method, which uses silicone oil as a base oil, lithium soap, and polytetrafluoroethylene (PTFE). Although PTFE is introduced to enhance performance, the compatibility problem caused by the polarity difference between silicone oil and lithium soap is not solved. The system is still a heterogeneous dispersion system, and there is still room for improvement in structural stability under extreme working conditions. Another example is patent document CN108822938A, which discloses a mixed lithium-based grease for improving dropping point and thermal stability, and its preparation method. It uses mineral oil or silicone oil, combined with lithium soap and an inorganic thickener (such as fumed silica). This approach mainly focuses on improving the dropping point but does not address the interfacial compatibility problem between the base oil and the thickener through chemical means (such as cyclosiloxane rearrangement), making it difficult to achieve a truly "homogeneous" sealing effect.
[0005] In summary, existing lithium-based silicone oil sealing materials generally suffer from problems such as uneven microstructure, weak resistance to extreme working conditions, and poor reliability in long-term use. These issues make it difficult to meet the stringent requirements of high-end mechanical equipment for long service life, high stability, wide temperature range, and high load, significantly limiting the widespread application of lithium-based lubricants in high-end industrial fields. Therefore, a new technical solution is needed to address these problems. Summary of the Invention
[0006] The purpose of this invention is to provide a lithium-based silicone oil homogeneous sealing material, its preparation method, and its application, in order to solve the problems mentioned in the background art. At present, lithium-based silicone oil sealing materials are difficult to meet the stringent requirements of high-end mechanical equipment for long service life, high stability, wide temperature range, and high load, which greatly limits the in-depth application of lithium-based grease in high-end industrial fields. They generally suffer from problems such as uneven microstructure, weak resistance to extreme working conditions, and poor reliability in long-term use.
[0007] To achieve the above objectives, the present invention provides the following three technical solutions: Firstly, this invention provides a lithium-based silicone oil homogeneous sealing material, composed of the following raw material components by mass percentage: 60-85 wt.% silicone oil base oil, 5-20 wt.% lithium-based thickener, 1-15 wt.% polytetrafluoroethylene, 1-5 wt.% fumed silica, and 1-5 wt.% cyclosiloxane, wherein the sum of the mass percentages of each raw material component is 100%; wherein the silicone oil base oil is polydimethylsiloxane, and the kinematic viscosity of the polydimethylsiloxane at 25°C is 200-300 mm² / s; the lithium-based thickener is lithium fatty acid soap; the particle size of the polytetrafluoroethylene is 0.1-50 μm; the particle size of the fumed silica is 5-50 nm, and its specific surface area is 150-400 m² / g.
[0008] Secondly, this invention provides a method for preparing a lithium-based silicone oil homogeneous sealing material, comprising the following specific steps: S1. Matrix preparation: Take the formula amount of silicone base oil and heat it to 60-100℃. Under constant temperature stirring conditions, add the formula amount of lithium-based thickener and stir until uniform to form a uniform basic structure network system. The stirring speed is 300-800 r / min. S2, Nanocomposite Modification: Add the formulated amount of fumed silica and cyclosiloxane to the system obtained in S1, and mix them by high shear dispersion to construct a nano-reinforced composite structure. The high shear dispersion speed is 3000-5000 r / min, and the total mixing time is 1-5 h. S3. High-temperature heat treatment: The mixture obtained in S2 is heated to 180-200℃ and subjected to isothermal heat treatment for 0.5-1 h to stabilize the system structure. S4. Low-temperature modification molding: When the heat-treated system is slowly cooled to below 100℃, the formula amount of polytetrafluoroethylene is added, and the system is continuously stirred until it is completely cooled. The material is discharged to obtain a lithium-based silicone oil homogeneous sealing material. The cooling rate is 2-5℃ / min, and the cooling method is natural cooling or programmed temperature control cooling. No ice water bath or forced air cooling is used throughout the process.
[0009] The third aspect is to apply the prepared lithium-based silicone oil homogeneous sealing material to automotive parts sealing and structural sealing under high-temperature conditions of 150-300℃.
[0010] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention uses cyclosiloxane as a chemical structure regulator to induce a siloxane rearrangement reaction in the system under high temperature (180-200℃) conditions. After the cyclosiloxane ring opens, it forms chemical bonds or strong physical entanglements with the silicone oil molecular chain and the active sites on the lithium soap surface. This eliminates the interfacial tension between the silicone oil phase and the lithium soap phase at the molecular level, transforming the system from a heterogeneous structure to a thermodynamically stable homogeneous structure. Based on this, multi-scale synergistic enhancement of lithium-based thickener, PTFE, and fumed silica is achieved, resulting in a sealing material with significantly better comprehensive performance than existing technologies. This completely eliminates the risk of oil leakage and delamination failure during storage and high-temperature static placement, and solves the colloidal stability shortcomings that existing technologies cannot eradicate.
[0011] 2. This invention uses cyclosiloxanes to build a "communication bridge," transforming a multi-component system from a "physical mixture" into a "chemically bonded homogeneous composite material," achieving true synergistic enhancement. Specifically: a lithium-based thickener constructs a basic three-dimensional network framework in situ, providing initial mechanical support and structural constraints for the system; fumed silica (particle size 5–50 nm, specific surface area 150–400 m² / g) is embedded in this network as high-specific-surface-area nanoparticles, forming a high-strength multi-scale composite support structure through physical adsorption and interfacial interactions; PTFE (particle size 0.1–50 μm) is uniformly distributed in the system as a solid functional dispersed phase, forming a low-shear-resistance migration layer at the friction interface under external shear; and the role of cyclosiloxanes is to eliminate interfacial incompatibilities between components at the chemical level, allowing the three functional components (thickener network, inorganic nano-reinforcing phase, and solid lubricating dispersed phase) to truly "take their place," forming a synergistic cooperation in three-dimensional space rather than existing in isolation.
[0012] 3. This invention, through the design of preheating and stirring the silicone oil base oil before blending, ensures the full dispersion and initial network construction of the lithium-based thickener in the silicone oil base oil. This avoids structural damage to the lithium soap at excessively high temperatures and ensures sufficient fluidity of the system to promote uniform mixing. The use of high-shear dispersion combined with the simultaneous addition of cyclosiloxane and fumed silica achieves full deagglomeration and uniform distribution of nanoparticles in the system. This step takes 1 to 5 hours, ensuring the full progress of the chemical rearrangement reaction. The design of isothermal heat treatment at 180 to 200°C ensures the activation energy requirements of the cyclosiloxane ring-opening rearrangement reaction while remaining within the stable temperature window of the lithium-based thickener, demonstrating a precise balance between chemical reaction kinetics and material thermal stability. Meanwhile, this step also has a vacuum degassing function, which can remove low molecular weight volatiles in the system and further improve the high temperature stability of the material. Natural cooling or programmed temperature control is used to slowly cool down the material, eliminating forced cooling operations, so that chemical rearrangement and structural rearrangement have sufficient "structural relaxation time", thereby ensuring that the homogeneous structure can transition from the metastable state to the thermodynamically stable state.
[0013] 4. The lithium-based silicone oil homogeneous sealing material prepared by this invention exhibits excellent high-temperature stability. Its stable homogeneous structure and multi-scale composite network enable it to maintain stable performance within a high-temperature range of 150℃ to 300℃, effectively overcoming the shortcomings of traditional lithium-based greases, such as easy softening and loss at high temperatures, and the poor mechanical stability of ordinary silicone greases. It is particularly suitable for applications in automotive parts (such as clutch release bearings), aerospace, and high-end equipment manufacturing, where long-term, reliable sealing and lubrication are required under harsh conditions such as heavy loads, high speeds, and high temperatures. Attached Figure Description
[0014] Figure 1 This is a physical image of the lithium-based silicone oil homogeneous sealing material of the present invention; Figure 2 The image shows the AFM (atomic force microscope) morphology of the lithium-based silicone oil homogeneous sealing material of the present invention (scanning range is 2μm and 10μm). Detailed Implementation
[0015] The technical solution of the lithium-based silicone oil homogeneous sealing material of the present invention will be fully described below with reference to specific embodiments and comparative examples. The raw material ratio of each embodiment meets the requirement of 100% total mass fraction, and the preparation process follows the parameters limited by the present invention. At the same time, the micro morphology and macro stability performance are compared and tested to prove the technical advantages of the present invention. However, the scope of protection of the present invention is not limited to the following embodiments. Example 1:
[0016] This embodiment provides a lithium-based silicone oil homogeneous sealing material, the raw material composition and mass percentage of which are: silicone oil base oil 80 wt.%, lithium-based thickener 10 wt.%, polytetrafluoroethylene 5 wt.%, fumed silica 3 wt.%, and cyclosiloxane 2 wt.%. The silicone oil base oil is polydimethylsiloxane with a kinematic viscosity of 240 mm² / s at 25°C; the lithium-based thickener is lithium fatty acid soap; the polytetrafluoroethylene has a particle size of 5 μm; and the fumed silica has a particle size of 15 nm and a specific surface area of 200 m² / g.
[0017] The specific preparation steps for preparing a lithium-based silicone oil homogeneous sealing material based on the above raw materials are as follows: First, 80 wt.% polydimethylsiloxane was added to the preparation container and heated to 60°C. Then, 10 wt.% fatty acid lithium soap was added under constant temperature stirring conditions and stirred at 500 r / min until homogeneous, forming a uniform basic lithium soap three-dimensional network system. Secondly, 3 wt.% fumed silica and 2 wt.% cyclosiloxane were added to the system and mixed by high shear dispersion. The high shear dispersion speed was 4000 r / min and the total mixing time was 3 h, so that the system gradually formed a uniformly distributed nano-reinforced composite structure. Then, the temperature was raised to 190℃ for vacuum degassing and structural regulation treatment (the system was kept at 190℃ and a vacuum of not less than -0.095MPa for 0.75h. On the one hand, the high temperature and vacuum were used to remove low-cyclic siloxanes and catalyst decomposition residues to complete the purification of the system; on the other hand, the temperature conditions were used to promote the chemical bridging reaction between cyclic siloxanes and the system interface, as well as the full swelling and rearrangement of lithium soap groups, thereby achieving uniform regulation of the microstructure). The system was kept at 190℃ for 0.75h to stabilize the structure. Finally, the mixture was allowed to cool naturally at a rate of 3°C / min until it reached below 100°C. Then, 5 wt.% polytetrafluoroethylene was added, and the mixture was stirred continuously until the system was completely cooled. The product was then discharged, yielding the milky white, uniform paste-like lithium-based silicone oil homogeneous sealing material of this embodiment (e.g., Figure 1 (As shown). Example 2:
[0018] This embodiment provides a lithium-based silicone oil homogeneous sealing material, the raw material composition and mass percentage of which are: silicone oil base oil 82 wt.%, lithium-based thickener 8 wt.%, polytetrafluoroethylene 4 wt.%, fumed silica 4 wt.%, and cyclosiloxane 2 wt.%. The silicone oil base oil is polydimethylsiloxane with a kinematic viscosity of 240 mm² / s at 25°C; the lithium-based thickener is lithium fatty acid soap; the polytetrafluoroethylene has a particle size of 10 μm; and the fumed silica has a particle size of 20 nm and a specific surface area of 250 m² / g.
[0019] The specific preparation steps for preparing a lithium-based silicone oil homogeneous sealing material based on the above raw materials are as follows: First, 82 wt.% polydimethylsiloxane was added to the preparation container and heated to 60°C. Then, 8 wt.% fatty acid lithium soap was added under constant temperature stirring conditions and stirred at 500 r / min until uniformly mixed to form a uniform basic lithium soap three-dimensional network system. Secondly, 4 wt.% fumed silica and 2 wt.% cyclosiloxane were added to the system and mixed by high shear dispersion. The high shear dispersion speed was 4000 r / min and the total mixing time was 3 h, so that the system gradually formed a uniformly distributed nano-reinforced composite structure. Then, the temperature was raised to 190℃ for vacuum degassing and structural regulation treatment (the system was kept at 190℃ and a vacuum of not less than -0.095MPa for 0.75h. On the one hand, the high temperature and vacuum were used to remove low-cyclic siloxanes and catalyst decomposition residues to complete the purification of the system; on the other hand, the temperature conditions were used to promote the chemical bridging reaction between cyclic siloxanes and the system interface, as well as the full swelling and rearrangement of lithium soap groups, thereby achieving uniform regulation of the microstructure). The system was kept at 190℃ for 0.75h to stabilize the structure. Finally, the mixture was allowed to cool naturally at a rate of 3°C / min until it was slowly cooled to below 100°C. Then, 4 wt.% polytetrafluoroethylene was added, and the mixture was stirred continuously until it was completely cooled. The mixture was then discharged to obtain the milky white, uniform paste-like lithium-based silicone oil homogeneous sealing material of this embodiment. Example 3:
[0020] This embodiment provides a lithium-based silicone oil homogeneous sealing material, the raw material composition and mass percentage of which are: silicone oil base oil 75 wt.%, lithium-based thickener 12 wt.%, polytetrafluoroethylene 8 wt.%, fumed silica 3 wt.%, and cyclosiloxane 2 wt.%. The silicone oil base oil is polydimethylsiloxane with a kinematic viscosity of 280 mm² / s at 25°C; the lithium-based thickener is lithium fatty acid soap; the polytetrafluoroethylene has a particle size of 20 μm; and the fumed silica has a particle size of 10 nm and a specific surface area of 300 m² / g.
[0021] The specific preparation steps for preparing a lithium-based silicone oil homogeneous sealing material based on the above raw materials are as follows: First, 75 wt.% polydimethylsiloxane was added to the preparation container and heated to 60°C. Then, 12 wt.% fatty acid lithium soap was added under constant temperature stirring conditions and stirred at 600 r / min until uniformly mixed to form a uniform basic lithium soap three-dimensional network system. Secondly, 3 wt.% fumed silica and 2 wt.% cyclosiloxane were added to the system and mixed by high shear dispersion. The high shear dispersion speed was 4500 r / min and the total mixing time was 4h, so that the system gradually formed a uniformly distributed nano-reinforced composite structure. Then, the temperature was raised to 200℃ for vacuum degassing and structural regulation treatment (the system was kept at 200℃ and a vacuum of not less than -0.095MPa for 1 hour. On the one hand, the high temperature vacuum was used to remove low-cyclic siloxanes and catalyst decomposition residues to complete the purification of the system; on the other hand, the temperature conditions were used to promote the chemical bridging reaction between cyclic siloxanes and the system interface, as well as the full swelling and rearrangement of lithium soap groups, thereby achieving uniform regulation of the microstructure). The system was kept at this temperature for 1 hour to stabilize the structure. Finally, the mixture was allowed to cool naturally at a cooling rate of 4°C / min until it was slowly cooled to below 100°C. Then, 8 wt.% polytetrafluoroethylene was added, and the mixture was stirred continuously until it was completely cooled. The mixture was then discharged to obtain the milky white, uniform paste-like lithium-based silicone oil homogeneous sealing material of this embodiment.
[0022] Comparative Example 1: This comparative example provides a sealing material and its preparation method. The raw material composition does not contain cyclosiloxanes, and the remaining raw material components and proportions are the same as in Example 1, namely: 82 wt.% silicone oil base oil, 10 wt.% lithium-based thickener, 5 wt.% polytetrafluoroethylene (PTFE), and 3 wt.% fumed silica. The specifications of the silicone oil base oil, lithium-based thickener, PTFE, and fumed silica are consistent with those in Example 1.
[0023] The preparation method follows the steps of Example 1, except that cyclosiloxane is not added in step two. The remaining operations and process parameters are the same as in Example 1. The specific steps are as follows: 82 wt.% silicone oil base oil is heated to 60°C, 10 wt.% lithium-based thickener is added and stirred at 500 r / min; 3 wt.% fumed silica is added and dispersed at 4000 r / min for 3 h under high shear; the temperature is raised to 190°C for 0.75 h heat treatment; the temperature is lowered to below 100°C and the formulated amount of polytetrafluoroethylene is added, stirred and cooled before discharge.
[0024] Comparative Example 2: This comparative example provides a sealing material and its preparation method. The raw material composition does not include fumed silica. The remaining raw material components and proportions are the same as in Example 1, namely: 82 wt.% silicone oil base oil, 11 wt.% lithium-based thickener, 5 wt.% polytetrafluoroethylene, and 2 wt.% cyclosiloxane. The specifications of the silicone oil base oil, lithium-based thickener, polytetrafluoroethylene, and cyclosiloxane are consistent with those in Example 1.
[0025] The preparation method follows the steps of Example 1, except that fumed silica is not added in step two. The remaining operations and process parameters are the same as in Example 1. The specific steps are as follows: 82 wt.% silicone oil base oil is heated to 60°C, 11 wt.% lithium-based thickener is added and stirred at 500 r / min; 2 wt.% cyclosiloxane is added and dispersed at 4000 r / min under high shear for 3 h; the temperature is raised to 190°C for 0.75 h heat treatment; the temperature is lowered to below 100°C and the formulated amount of polytetrafluoroethylene is added, stirred and cooled before discharge.
[0026] The sealing materials prepared in Examples 1-2 and Comparative Examples 1-2 were characterized by their microstructure and tested by their macroscopic properties.
[0027] AFM (Atomic Force Microscopy) test results are as follows Figure 2 As shown, significant differences in microstructure were observed in different systems at scanning scales of 2 μm and 10 μm. In Examples 1 (Fig. a) and 2 (Fig. b), the system surface exhibited uniformly distributed nanoscale structures with small and continuous particle size, indicating good dispersibility and structural continuity of the components within the system, and a relatively complete homogeneous structure. In contrast, obvious local agglomeration and uneven dispersion were observed in Comparative Examples 1 (Fig. c) and 2 (Fig. d), especially at the 10 μm scanning range, indicating that the system is difficult to form a stable homogeneous structure in the absence of cyclosiloxanes or fumed silica.
[0028] The working cone penetration and drum stability test results for each system are shown in the table below: .
[0029] In the working cone penetration test, the cone penetration values of Example 1 and Example 2 were 318 and 324, respectively, and the cone penetration values of Comparative Example 1 and Comparative Example 2 were 323 and 319, respectively. The cone penetration values of the four groups of samples were not significantly different and were all within a moderate range, indicating that each system has good structural flexibility and machinability.
[0030] In the drum stability test, the drum stability values of Example 1 and Example 2 were 11 and 15, respectively, indicating that they could maintain high structural stability and resistance to structural degradation under long-term shear and thermal conditions. In contrast, the drum stability values of Comparative Example 1 and Comparative Example 2 were as high as 67 and 56, respectively, indicating that their structural damage was more severe after shear and thermal effects, and the stability of the system decreased significantly.
[0031] The combined AFM morphology and macroscopic performance test results show that the system in the example exhibits a more uniform and continuous distribution in its microstructure, and demonstrates excellent structural stability in both cone penetration and drum stability tests. This indicates that by introducing cyclosiloxanes to regulate the dispersion behavior of the system and constructing a multi-scale composite network structure by combining fumed silica and lithium-based structural components, the homogeneous structure formation capability and long-term service stability of the system can be significantly improved. The comparative system, lacking key structural regulating components, exhibits poor microstructural uniformity and is prone to structural damage and performance degradation under high temperature and shear conditions, further verifying the effectiveness and necessity of the technical solution of this invention.
Claims
1. A lithium-based silicone oil homogeneous sealing material, characterized in that, It is composed of the following raw material components by mass percentage: 60-85 wt.% silicone base oil, 5-20 wt.% lithium-based thickener, 1-15 wt.% polytetrafluoroethylene, 1-5 wt.% fumed silica and 1-5 wt.% cyclosiloxane, and the sum of the mass percentages of each raw material component is 100%.
2. The lithium-based silicone oil homogeneous sealing material according to claim 1, characterized in that, The silicone oil base oil is polydimethylsiloxane, and the kinematic viscosity of polydimethylsiloxane at 25°C is 200–300 mmHg. 2 / s.
3. The lithium-based silicone oil homogeneous sealing material according to claim 1, characterized in that, The lithium-based thickener is a fatty acid lithium soap.
4. The lithium-based silicone oil homogeneous sealing material according to claim 1, characterized in that, The particle size of the polytetrafluoroethylene is 0.1–50 μm.
5. The lithium-based silicone oil homogeneous sealing material according to claim 1, characterized in that, The fumed silica has a particle size of 5–50 nm and a specific surface area of 150–400 m². 2 / g.
6. A method for preparing a lithium-based silicone oil homogeneous sealing material according to any one of claims 1-5, characterized in that, The specific steps include the following: S1. Matrix preparation: Take the formula amount of silicone base oil and heat it to 60-100℃. Under constant temperature stirring, add the formula amount of lithium-based thickener and stir until uniformly mixed to form a uniform basic structure network system. S2, Nanocomposite Modification: Add the prescribed amount of fumed silica and cyclosiloxane to the system obtained in S1, and mix them through high shear dispersion to construct a nano-reinforced composite structure; S3. High-temperature heat treatment: The mixture obtained in S2 is heated to 180-200℃ for isothermal heat treatment to stabilize the system structure. S4. Low-temperature modification molding: When the heat-treated system is slowly cooled to below 100℃, the formulated amount of polytetrafluoroethylene is added, and the system is continuously stirred until it is completely cooled. The material is then discharged to obtain a lithium-based silicone oil homogeneous sealing material.
7. The method for preparing a lithium-based silicone oil homogeneous sealing material according to claim 6, characterized in that, In S1, the stirring speed is 300–800 r / min; in S2, the high-shear dispersion speed is 3000–5000 r / min; and the total mixing time is 1–5 h.
8. The method for preparing a lithium-based silicone oil homogeneous sealing material according to claim 6, characterized in that, In S3, the constant temperature holding time is 0.5 to 1 hour.
9. The method for preparing a lithium-based silicone oil homogeneous sealing material according to claim 6, characterized in that, In S4, the cooling rate is 2-5℃ / min, and the cooling method is natural cooling or programmed temperature control cooling, without using ice water bath or forced air cooling throughout the process.
10. The application of the lithium-based silicone oil homogeneous sealing material according to any one of claims 1-5 in automotive component sealing and structural sealing under high temperature conditions of 150-300℃.
Citation Information
Patent Citations
High-performance silicone-base lubricating grease composition and preparation method thereof
CN106635347A
Mixed lithium-based grease for improving dropping point and thermal stability, and preparation method thereof
CN108822938A
Lithium-based lubricating grease composition and preparation method thereof
CN114703004A
